Oxford handbook of orthopaedics and trauma - Bowden, Gavin (Oxford : Oxford University Press, 2010)
This handbook provides easily accessible information on orthopaedics and trauma, clearly presenting the salient features of a range of conditions and their treatment, and enabling junior doctors and students to confidently apply the knowledge to clinical activities.
Includes bibliographical references and index.
Keywords: This handbook provides easily accessible information on orthopaedics and trauma, clearly presenting the salient features of a range of conditions and their treatment, and enabling junior doctors and students to confidently apply the knowledge to clinical activities; Musculoskeletal Diseases; Musculoskeletal System